السرد العجائبي في قصص الأطفال لنماذج مختارة - واغد, روميصاء; حمادي, عبد الرؤوف; عمراني, فوزي; بوذينة, ليلى; علاق, هديل (University of Eloued جامعة الوادي, 2024)
إن العجائبية في القصص الموجهة إلى الطفل، بعناصرها (العتبات، الشخصيات، الزمان، والمكان) تقينة يستخدمها الكاتب لتأثير على هءا متلقي صغير، فهي تساعده في بناء منظومة اخلاقيه وإنسانيه، من خلال مايتم توظيفه في هذه القصص، فكل عنصر منها يأثر عليه من جانب معين، فالعتبات تعد عنصر أولي في عملية التأثير من خلال الصورة وعنوان وتشكيلهم، أما بالنسبة إلى الشخصيات فهي عنصر اساسي في تكوين وبلورة شخصيت وميولات وأفكار هذا المتلقي، وكذلك هو الحال بالنسبة إلى توظيف بنية الزمان والمكان فكلاهما يساعدانه في فتح أفاق جديده في مخيلته. The fantastic in the stories addressed to children, with their elements (thresholds, characters, time, and place), is a technique used by the writer to influence this young recipient. It helps him build a moral and humane system, through what is employed in these stories. Each element of them affects him from one side. Certainly, thresholds are considered a primary element in the process of influence through the image, title, and formation of them. As for the characters, they are an essential element in forming and crystallizing the personality, inclinations, and ideas of this recipient. The same is true of employing the structure of time and place, both of which help him open new horizons in his imagination.
دراسات أدبية
Keywords: : العجائبية، قصص الأطفال، فاعلية التأثير; Fantastic; children’s stories; effectiveness of influence